2005
DOI: 10.2139/ssrn.652701
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Effects of Human Rights

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 59 publications
2
22
1
Order By: Relevance
“…This accords with the theoretical reasoning by Farber (2002) who views governmental obedience to basic rights as a signal to investors of a government's commitment to a broader set of legal rules -including property rights. The result also accords with empirical results by Blume and Voigt (2007) who found that human rights are significantly conducive to productivity and investment in physical capital.…”
Section: Democracy and Economic Liberalization In (Almost) Two Decadesupporting
confidence: 91%
“…This accords with the theoretical reasoning by Farber (2002) who views governmental obedience to basic rights as a signal to investors of a government's commitment to a broader set of legal rules -including property rights. The result also accords with empirical results by Blume and Voigt (2007) who found that human rights are significantly conducive to productivity and investment in physical capital.…”
Section: Democracy and Economic Liberalization In (Almost) Two Decadesupporting
confidence: 91%
“…Koob, Jørgensen and Sano (2017) find no evidence that freedom and participation rights in different regions of the world are harmful to growth: it either promotes growth or has no effect on growth. Blume and Voigt (2007) examine the effect of four different categories of human rights on economic growth and welfare. Precisely, they are interested in the impact of basic human rights, property rights, civil rights and social rights on investment and productivity.…”
Section: IImentioning
confidence: 99%
“…See Spolaore and Wacziarg (2013) for a recent review. Somewhat relatedly, Blume and Voigt (2007) empirically examine the effects of well-known cross-country human rights (and other rights) measures on economic outcomes like investment, economic growth and total factor productivity. The authors find that political, property, civil and emancipatory rights are positive associates of economic outcome.…”
Section: Constitutions and The Environmentmentioning
confidence: 99%